Knowledge and Practices of HealthCare Workers Regarding of Medical Waste Management in Hospitals of Al Najaf Governorate - Naseem B. Saadoon; Luma H.Ali; Suha A. Kadum (Journal of Techniques)
Medical waste (MW) is a serious problem in many developing countries. Iraq being one of them it faces challenges in waste management due to the environmental and human health risks.